Which membership matters? External vs. internal determinants of institutional change in transition countries - Thorsten Drautzburg; Inna Melnykovska; Rainer Schweickert (Kiel Institute for the World Economy (IfW), 2008)
This paper analyses potential internal and external determinants of institutional change as measured by the World Bank Governance Indicators (WBGI) based on a panel of 25 transition countries for the period from 1996 to 2005. We show that natural resources and capital inflows exert an insignificant or negative influence and that economic policy allows to break path-dependency. Most importantly, however, we are able to show that incentives provided by NATO membership are important for institutional development and even more robust than variables measuring the integration into the EU. This allows for some optimism about the effectiveness of ENP policies and supports the argument that NATO, offering regional security, may provide significant additional incentives for good governance.
Keywords: P30; F20; O19; F15; P20; F50; 330; NATO; Transition Economies; Institutional Change; Governance; EU; Mitgliedschaft; Bündnissystem; EU-Erweiterung; Ökonomischer Anreiz; Institutioneller Wandel; Good Governance; Übergangswirtschaft; GUS-Staaten; NATO-Staaten; EU-Staaten